Meta’s privacy practices on Facebook: compliance, integrity, and a framework for excellence - Marco Tulio Daza-Ramírez (Discover Artificial Intelligence)
Abstract This paper examines Meta’s privacy practices on its Facebook platform through the lenses of compliance with data protection laws, the integrity of its stakeholder relationships, and the pursuit of excellence based on a Neo-Aristotelian virtue ethics framework. The paper highlights the tension between privacy protection and business objectives by analyzing Meta’s reliance on user data for its advertising-driven business model. It critiques the limitations of compliance with legal standards in the US and the EU, showing that fines and regulations often fail to deter the company’s invasive data practices. Integrity-based approaches are similarly inadequate, as they are frequently co-opted for reputational management rather than promoting genuine ethical behavior. This paper advocates for a virtue ethics approach grounded in the pursuit of human flourishing and the common good. Facebook can advance these aims by deepening its commitment to its MacIntyrean practice—namely, enabling social connections—and realizing its internal good of facilitating “global meaningful social interactions.” Achieving this requires not only embedding virtues within the company’s operational culture but also fostering their cultivation among stakeholders. The analysis concludes that reorienting Facebook toward ethical excellence could both safeguard user privacy, mitigate associated harms, and establish a new benchmark for corporate responsibility, thereby contributing meaningfully to the common good.